Bygga om och till för dikor - Olsson, Martin (2008)
To be a farmer and have suckler cows is a difficult combination especially considering the economy. Because of the increased feed costs, the margins have become tighter. The meat price from beef cattle has increased a little when this text is written (spring, 2008), but not so much that it covers the cost for feed etc.